Prognosis of neutrophil-to-lymphocyte ratio in clinical early-stage tongue (cT1/T2N0) cancer - Wu, Ching-Nung (Onco Targets Ther, 2017)
BACKGROUND: Inflammation plays a role in the development of cancer. This study aims to analyze the prognostic value of the neutrophil-to-lymphocyte ratio (NLR) and other clinicopathological determinants in early-stage (cT1/T2N0) tongue cancer. MATERIALS AND METHODS: A total of 262 patients were selected from our institute’s cancer database between 2004 and 2011. Optimal cutoff value of NLR and lymph node density (LND) were determined statistically using receiver operating characteristic curve analysis for survival prediction. The 5-year overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS) rates were estimated using the Kaplan–Meier method. RESULTS: The results showed that, in this cohort, the optimal cutoff value of NLR was 2.95 and for LND, it was 0.031. Patients with NLR ≥2.95 correlated significantly with positive N classification (P=0.011), T2 classification (P=0.007), positive perineural invasion (P<0.001), and a tumor thickness of >5 mm (P=0.005). The 5-year OS among patients with NLR <2.95 was much higher than that in patients with NLR ≥2.95 (P<0.001). Similarly, the 5-year DSS among patients with NLR <2.95 was much higher than that in patients with NLR ≥2.95 (P=0.002). The 5-year DFS among patients with NLR <2.95 was much higher than that in patients with NLR ≥2.95 (P=0.004). The 5-year OS, DSS, and DFS were significantly reduced among patients with LND >0.031 compared to those with LND <0.031, respectively. In multivariate analysis, NLR, LND, and tumor thickness were independent prognostic factors for OS. CONCLUSION: Pretreatment NLR ≥2.95 is significantly correlated with a larger tumor, positive neck lymph node metastasis, and positive perineural invasion. Importantly, it indicates reduced survival rate. Therefore, if the NLR ≥2.95 in early-stage (cT1/T2N0) tongue cancer is noted preoperatively, it reveals more invasive tumor behavior clinically. Then, aggressive treatments, including elective neck dissection, become necessary.